Aural Attunement is a form of performative writing used to write about nonhuman affective relations in Emma Bennett’s Slideshow Birdshow (2013) - Rebecca Collins (Ambiances)
In this article aural attunement is put forward as a means of performative writing to attend closely to affective relations with nonhuman entities (namely birds). Embodied knowledge harnessed in the writing aims to emulate the experience of being a listening-spectator at Slideshow Birdshow (2013), a solo contemporary performance piece by Emma Bennett. Whilst it is recognised that non-representational theory is a catch-all term to describe affect, atmosphere, and lived experience occurring in the social and relational aspects of our daily lives, the articulation of such dimensions are complicated and not fully translatable into words. Here it is argued, through a critically-intimate writing practice, that contemporary performance and performative writing have much to offer to the ongoing debates within human geography in relation to this. The use of aural attunement to attend to micro-movements, vibrations, rhythm and tone indicate a more sensorial engagement thereby highlighting our affective relations with the nonhuman.